Visual Culture in Social Media: A Study on the Influence of Instagram on Aesthetics and Youth Culture Trends - Fauzi Eka Putra; Pepy Afrilian (MD Research Center, 2025)
This study examines the influence of visual aesthetics on Instagram in shaping social identity and user behavior, with a focus on how the visual standards on this platform affect how individuals express themselves. Using a literature review method, this research gathers and analyzes various relevant sources, including academic articles, journals, and previous research reports, to explore the impact of visual aesthetics on Instagram users. The main findings of this study show that the visual aesthetics on Instagram, which often create idealized representations of the self, play a significant role in the formation of individual social identity. Users, especially younger ones, are frequently influenced by the beauty standards and lifestyles promoted by influencers, reinforcing the tendency to compare themselves with more